Estrous behavior, ovulatory follicle dynamics, and corpus luteum size in Creole cows after spontaneous or prostaglandin F2α-induced estrous - Quezada Casasola Andrés; Avendaño Reyes Leonel; Macías Cruz Ulises; Ramírez Godínez José A; Rivas Cáceres Raymundo R (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: evaluation of reproductive behavior in Creole cows is important to determine several parameters, such as fertility, that show the physiologic reproductive mechanisms under different conditions. Therefore, the sequence of events such as ovulation and the subsequent formation of a corpus luteum need tobe considered to establish genetic improvement programs under synchronized or naturally-occurring estrous conditions. Objective: to evaluate the ovarian and behavioral estrous characteristics before, during and after prostaglandin F2α-induced or naturally occurring estrous in Creole cows. Methods: thirty Creole cows were subjected to estrous synchronization with PGF2α and observed continuously over five days to determine estrous onset and duration. Seventeen days after synchronized estrous detection, cows were observed during seven d to detect the naturally-occurring estrous and its duration. After the onset of both types of estrous the ovaries of each cow were ultrasounded every 8 h to determine diameter of the preovulatory follicle at deviation and its maximum diameter prior to ovulation, as well as its growth rate, time to ovulation and maximum diameter of the later corpus luteum. Results: time of appearance and duration of synchronized and spontaneous estrous were similar (p>0.1). Diameters of the dominant follicle at deviation and prior to ovulation were similar in both types of estrous. Nevertheless, growth rate (mm/d) of the preovulatory follicle was higher (p < 0.05) in synchronized estrous. However, time from onset of synchronized estrous to ovulation was longer (p < 0.01).Diameter of corpus luteum 10 d after ovulation was similar in both types of estrous. Results indicate that growth rate of follicle and time from synchronized or spontaneous estrous to ovulation must be considered for estrous cycle manipulation and artificial insemination of Creole cows. Conclusion: a higher proportion of Creole cows show heat during nighttime, growth rate of ovulatory follicle is higher during synchronized estrous, and time from onset of synchronized estrous to ovulation is longer, when compared with spontaneous estrous.